Body Image Self-Perception and Risky Eating Behaviors in Medicine Undergraduate Students in Xalapa, Veracruz, Mexico (2014) (2019)
Introduction: The current beauty standard is associated with thinness, a situation that alters the body perception and can lead to the development of an eating disorder. Objective: To determine the relationship between the indexes of body image dissatisfaction and body image distortion and risky eating behaviors (REB) in a university population of medicine students in Veracruz, Mexico. Materials and Methods: Cross-sectional analytical study, with a sample of 187 students. A register was drawn up that included the SFS-test to evaluate the body image and to estimate the indices of dissatisfaction and distortion of the body image, the Brief Questionnaire of Risky Eating Behaviors validated in Mexican population, as well as social variables. A descriptive analysis was carried out with basic measures of frequency and dispersion, bivariate and multimodal analyses were performed too. Results: 43 % were female, and the average age was 21 (± 1.7) similar in both sexes. The prevalence of high risk of reb was 8.6 %, higher in men (9.4 % versus 7.4 %) and medium risk (23.5 %) with the distribution reversed by sex (28.4 % in women and 19.8 % in men). The dissatisfaction index was 59.4 % covering those who perceived having a higher weight than they would like to have. Concerning the distortion of the own body image it was observed that 41.2 % supposed to haveing a higher weight than what resulted from the anthropometric evaluation. Discussion: Dissatisfaction rates showed a positive correlation gradient with rebs, being this more evident in men.